PENGARUH DEWAN KOMISARIS INDEPENDEN KOMPLEKSITAS PERUSAHAAN DAN KONVERGENSI IFRS TERHADAP FEE AUDIT PADA PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BEI - Renzy Octa Riwanti Renzy; Meutia Dewi; Iqlima Azhar (Jurnal Mahasiswa Akuntansi Samudra, 2022)
This study aims to determine the effect of independent commissioners, company complexity and IFRS convergence on audit fees at Property and Real Estate companies listed on the Indonesian Stock Exchange (IDX). By using the purposive sampling method, a sample of 6 companies can be obtained. The data analysis method used is the classical assumption test such as normality test, multicollinearity test, heteroscedasticity test and autocorrelation test and hypothesis testing such as multiple linear regression test, t test, F test, and R2 test using SPSS as an analytical tool. The results of the multiple linear regression equation Y= 15,679-0.676X1+0.170X2-0.036X3. The constant of 15,679 is the value of the audit fee at the Property and Real Estate company which is constant (fixed), the regression coefficient of the independent board of commissioners variable, and the IFRS convergence is negative for the audit fee, while the complexity of the company is positive for the audit fee. Partially, independent board of commissioners, company complexity and IFRS convergence have no significant effect on audit fees. And simultaneously independent board of commissioners, company complexity and IFRS convergence show no significant effect on audit fees. From the coefficient of determination test results obtained a value of 22.1% while the remaining 77.9% is influenced by other variables not included in this study.